Bioactive substances of some herbals and their effectiveness as antioxidant, antibacteria and antifungi - Arnold P. Sinurat; Elizabeth Wina; Susana I.W. Rakhmani; T. Wardhani; Tuti Haryati; T. Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2018)
A study was conducted to explore the bioactive substances of some local plants in order to find their effectiveness as antioxidant, antibacteria and antifungi to be used as feed additives. Twelve plants material were used in this study. The total phenol, tannin and saponin contents in the plant extract were assayed. The extracts were also assayed on their antioxidant activities and on their ability to depress in vitro gas production of microbes obtained from chicken’s guts, their ability to inhibit growth of bacteria (E. coli and Salmonella enteridis) and fungi (A. niger). The results showed that the highest total phenol and total tannin contents were found in clove leaf extract, while the highest saponin content was found in Sapindus rarak fruit pericarp. The highest antioxidant activity was found in the leaffruit extract. Gas produced by microorganims was reduced to the level similar to antibiotic addition were found with addition of hexane- extract of leaffruit, kapok seed or methanol- extract of mangosteen fruit rind pulp or clove leaves. The best inhibitory effect on E. coli growth (measured by clearing zone) was found in methanol extract of S. rarak fruit. However, the most effective growth inhibitor for both E. coli and Salmonella was the liquid smoke of cashew nut shell. The best growth inhibitor for fungal growth was found in extract of clove leaves. Therefore, clove leaves extract (anti fungi), liquid smoke of cashew nut shell (antibacteria) and leaffruit (antioxidant) may have potential to produce feed additives to substitute antibiotic growth promoters.